2016
DOI: 10.3390/ijgi5090157
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Patient bypass Behavior Using Taxi Trip Origin–Destination (OD) Data

Abstract: Abstract:Many patients prefer to use the best hospitals even if there are one or more other hospitals closer to their homes; this behavior is called "hospital bypass behavior". Because this behavior can be problematic in urban areas, it is important that it be reduced. In this paper, the taxi GPS data of Beijing and Suzhou were used to measure hospital bypass behavior. The "bypass behavior index" (BBI) represents the bypass behavior for each hospital. The results indicated that the mean hospital bypass trip di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…The study indicates that patients often prefer to visit healthcare facilities farther away from home instead of closer ones, and this is a common phenomenon. This bypass behavior [ 22 ] results in some users of the healthcare facilities in a catchment area not being included in it or some residents of a particular catchment area not visiting the facilities within it. In other words, the arbitrarily defined catchments and subzones, which are based on theoretical spatial barriers, may not represent the actual distribution of patients for the healthcare facilities in a study area.…”
Section: Introductionmentioning
confidence: 99%
“…The study indicates that patients often prefer to visit healthcare facilities farther away from home instead of closer ones, and this is a common phenomenon. This bypass behavior [ 22 ] results in some users of the healthcare facilities in a catchment area not being included in it or some residents of a particular catchment area not visiting the facilities within it. In other words, the arbitrarily defined catchments and subzones, which are based on theoretical spatial barriers, may not represent the actual distribution of patients for the healthcare facilities in a study area.…”
Section: Introductionmentioning
confidence: 99%
“…Patients prefer to choose the best hospitals, and the best hospitals always locate in crowed areas. In time, healthcare accessibility varies greatly, which causes spatial heterogeneity for the high-quality hospitals [15]. So the new construction of hospitals should be planned considering population, distance, transportation, and other factors [3,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the taxi data provide useful information at individual levels, they cannot differentiate the specific purposes of hospital visits. Although the taxi data we used only cover a single week in a single year, the data volume is comparable with (or even exceeds) those in many other applications using taxi data (Chen, Yuan et al, ; Liu et al, ; Yang et al, ; Yue et al, ). However, the one‐week data may not represent all of the situations encountered during the whole year.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, to study the health care problems in China from a spatial perspective, one should consider making best use of the available data at hand, such as the taxi trajectories data. In a recent study, Yang et al () suggested that the widespread bypass behavior of Chinese patients makes them more willing to pay extra transportation fares (e.g., taking a taxi) in order to visit high‐level hospitals. Kong, Liu, Wang, Tong, and Zhang () also demonstrated the usefulness of taxi data for the analysis of hospital characteristics in Beijing.…”
Section: Introductionmentioning
confidence: 99%